G. P. Kalantaevska, N. N. Prokopenko, S. V. Voropai. Literary environment and literary situation in Ukraine in 60 – 70’s of xx century in the context of the correspondence of B. Antonenko-Davydovych. - G. P. Kalantaevska; N. N. Prokopenko; S. V. Voropai (Philological Treatises, 2020)
The modern era is marked by confrontation between different ideological and conceptual worlds, which is caused mainly by controversial views on the Ukrainian history and a complicated historical path of the Ukrainian nation to a desired independence. In this struggle, the uncompromising words of the famous Ukrainian writer B. Antonenko-Davydovych sound especially acute. In the modern conditions, there is a necessity to make effective resistance to the active advent of the imperial ideology of the "Russian world". That is why the study of the opposition of B. Antonenko-Davydovych to russification of Ukrainian society by the totalitarian Soviet system and the destruction of Ukrainian creative intelligentsia in particular in the 60’s and 70’s of the twentieth century is very important. That is one of the means to protect modern youth from the threat of returning to the atmosphere of contempt and hatred of their native language and culture. In this context, the article provides a detailed analysis of the writer’s correspondence, in which he gave an honest assessment of the literary environment, opportunistic activity of Ukrainian editors and publishing houses, ethical-moral and professional qualities of officials from his environment. B. Antonenko-Davydovych also objectively told the nearest addressees about his struggle with a powerful campaign of Russification of all spheres of Ukrainian social life, about his open performances in the press in defense of his native word, which was forced out from education, science, art, even from the musical sphere. In the work of many writers, in the planning of the activity of publishing houses, B. Antonenko-Davydovych clearly noticed the signs of serving the interests of party leaders, the policies of the communist regime, revealing the ideological control by security structures, the phenomena of careerism, financial machinations, competition for material benefits and rewards, etc. The brazen imposition of Russian repertoires at the concerts both in Kyiv and villages, falsification of folk art in numerous folklore collections, or intentional discrimination of the Ukrainian word by printing primitive, low-art texts, - nothing of this got past the writer’s attention, because of his sensitivity to deception. In most of his colleagues, the writer noted the chronic fear, the willingness to serve the regime, the degradation of creativity, however he also noticed the literary figures of the highest European level. The denigrating of the honest writer’s name that was conditioned by his position regarding the protection of the rights of the Ukrainian language for its full functioning in Ukraine testified to the real threat of assimilation of Ukrainians, which was a continuation of the Valuyev’s policy of autocratic Russia. The study provides an opportunity to realize how dangerous a totalitarian state policy can be. Because it aims to cultivate the mood of fear, anxious expectation, uncertainty among cultural leaders, the dominance of censorship and the hidden propaganda influence of power structures on the activities of editors, publishers, scientific institutions. B. Antonenko-Davydovych’s intransigent position in protecting his native language in an aggressive Russification is a vivid example of the behavior of a patriotic personality, a representative of the cultural and artistic center, which is particularly relevant in our time and allows contemporaries to find answers to the challenges of today, in particular regarding the revival of Ukrainian language. 12©